The Effects of Brief Intervention on Medication Adherence Behaviors of Schizophrenic Patients - จันทร์สุข, ชวนนท์; จันทร์สุข, นฤมล; หร่ายลอย, อัฌชา (Journal of The Royal Thai Army Nurses, 2019)
This study was a quasi-experimental research. The objective of research were to compared the medication adherence behaviors of schizophrenic patients, before and after received the brief intervention ; and between the groups that were received the brief intervention with the groups received routine nursing care. The samples were selected by the purposive sampling technique to include the schizophrenic patients. They were divided into two groups: 30 patients who were provided with a nursing care as the control group , and the other 30 patients who received brief intervention as the experimental group by simple random sampling and matching the sample group in terms of gender, age and education level. The intervention instruments was the brief intervention. Data were collected using the questionnaires of medication adherence behaviors. Data were analyzed by frequency, percentage and t-test. The results of this study showed that: The experimental group’s mean score of the medication adherence behaviors were significantly higher than before involving the brief intervention ; and significantly higher than control group at the level .05 (p<.01).